Healthcare Utilization and Medical Cost of Gastrointestinal Reflux Disease in Non-tuberculous Mycobacterial Pulmonary Disease: A Population-Based Study, South Korea, 2009–2017 - Kim, Taehee; Yoon, Jai Hoon; Yang, Bumhee; Ryu, Jiin; Yoon, Chang Ki; Kim, Youlim; Sohn, Jang Won; Lee, Hyun; Choi, Hayoung (Frontiers in Medicine, 2022)
Gastroesophageal reflux disease (GERD) is a common non-respiratory comorbidity in patients with non-tuberculous mycobacterial pulmonary disease (NTM-PD). However, little is known about the association between GERD and healthcare utilization and medical costs of NTM-PD. Thus, we evaluated this association using the Health Insurance Review and Assessment Service National Patient Sample. NTM-PD patients with GERD had significantly higher healthcare use and spent a higher total on medical costs (5,098 vs. 2,675 USD/person/year) than those without GERD (P < 0.001 for all). Therefore, an appropriate management of GERD in NTM-PD patients can be an important factor to reduce the disease burden.